THE IMPACT OF PATENTS AND R&D COOPERATION ON R&D INVESTMENTS IN A DIFFERENTIATED GOODS INDUSTRY (The South East European Journal of Economics and Business, 2020)
In this paper, we consider the impact of patents and R&D cooperation on R&D investments in the oligopolistic industry with differentiated products. Four types of firms’ conduct are investigated: R&D competition without patents, R&D competition with patent protection, R&D cooperation, and the full industry cooperation. The obtained results suggest that patents do not necessarily promote R&D investments due to the existence of so called tournament effects. R&D cooperation stimulates R&D investments, but R&D cooperation provides sufficient incentives to create a full industry cartel. Such a cartel works to the detriment of consumers. Our analysis led us to the conclusion that for a relatively low level of R&D spillovers, the policy-makers should promote R&D competition without patent protection among oligopolistic firms. For a relatively high level of R&D spillovers, R&D cooperation enhances innovation, but the regulator should monitor the market for probable collusion.